Implementation of The Information Service Application Portal for Registration of Prospective Santri and Recording of School Activities Using The Extreme Programming Method - Nurmi Hidayasari; Mansur Mansur; Elfira Nurul Ilma; Dinda Anisa (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2023)
For Islamic boarding schools, the website functions as a medium of information and school introduction to the public. In order for prospective students to register easily, complete information is needed so that the boarding school can easily manage the data of prospective students. Apart from teaching and learning, teachers and students also have other activities at school. The categories of activities carried out by teachers are training, teaching, RPP (Learning Implementation Plans), and clubs or CCA (Co-Curricular Activities), while the categories of activities carried out by students are extracurricular activities, organizations, and competitions. All information on teacher and student activities requires data to be stored properly for a certain period of time. This study aims to build an information service application for registration of prospective students and recording of school activities using the extreme programming method. This application is made using the PHP programming language with the CodeIgniter framework, a MySQL database, and extreme programming as an application development method. Based on the tests carried out, this application can run on various browser applications, such as Google Chrome, Mozilla Firefox, and Microsoft Edge.